The Pentagon Spy - Dixon Franklin W.; Franklin W. Dixon (Canada Franklin W. Dixon, 1980)
Frank and Joe Hardy as they investigate the theft of antique weather vanes in Pennsylvania. Simultaneously, their father, Fenton Hardy, searches for a missing Navy employee and a top-secret document stolen from the Pentagon
Keywords: navigating high-stakes risks to gain access to classified information, sometimes while being monitored themselves; often referred to in the context of "spying" or whistleblowing on the Pentagon